Proceedings of the 49th Annual Design Automation Conference 2012
DOI: 10.1145/2228360.2228543
|View full text |Cite
|
Sign up to set email alerts
|

Alternate hammering test for application-specific DRAMs and an industrial case study

Abstract: This paper presents a novel memory test algorithm, named alternate hammering test, to detect the pairwise word-line hammering faults for application-specific DRAMs. Unlike previous hammering tests, which require excessively long test time, the alternate hammering test is designed scalable to industrial DRAM arrays by considering the array layout for potential fault sites and the highest DRAM-access frequency in real system applications. The effectiveness and efficiency of the proposed alternate hammering test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Second, bridges are a well-known class of DRAM faults in which conductive channels are formed between unrelated wires and/or capacitors [3,4]. One study on embedded DRAM (eDRAM) found that toggling a wordline could accelerate the flow of charge between two bridged cells [29]. Third, it has been reported that toggling a wordline for hundreds of hours can permanently damage it by hot-carrier injection [17].…”
Section: Mechanics Of Disturbance Errorsmentioning
confidence: 99%
“…Second, bridges are a well-known class of DRAM faults in which conductive channels are formed between unrelated wires and/or capacitors [3,4]. One study on embedded DRAM (eDRAM) found that toggling a wordline could accelerate the flow of charge between two bridged cells [29]. Third, it has been reported that toggling a wordline for hundreds of hours can permanently damage it by hot-carrier injection [17].…”
Section: Mechanics Of Disturbance Errorsmentioning
confidence: 99%
“…The Rowhammer bug has recently been studied [16,20,29] and the majority of off-the-shelf DRAM modules has been found vulnerable to bit flips using the clflush instruction. The clflush instruction flushes data from the cache, forcing the CPU to serve the next memory access from DRAM.…”
Section: The Rowhammer Bugmentioning
confidence: 99%
“…In 2014, Kim et al [44] showed that such bit errors can be caused in a DRAM row by rapidly accessing memory locations in adjacent DRAM rows (also known as row hammering [29]). To achieve these rapid DRAM accesses, data-caching mechanisms need to be bypassed, either by flushing the cache, e.g., using clflush [44], cache eviction [1,6,24], or uncached memory accesses [58].…”
Section: A the Rowhammer Bugmentioning
confidence: 99%